Das terras do Sem Fim aos Territórios do Agrohidronegócio: conflitos por terra e água no vale do São Francisco - Dourado, José Aparecido Lima [UNESP] (2015)
Public policies aimed at fostering irrigation in northeastern Brazil have promoted over the last four decades, profound changes in the agrarian space of semiarid region. Within the context of conservative modernization of agriculture, irrigation projects created by the National Department of Works Against Drought (DNOCS) and the Development Company of the Rio São Francisco and Parnaíba Valleys (CODEVASF) became the driving force for development regional economic and is, in many cases strongly linked to big business and the interests and external bodies, such as the Common Agricultural Policy (CAP) European. Public investment in water infrastructure works, fertile land, labor, labor supply and favorable weather conditions allowed the territorialization of agrohidronegócio in the valley of the São Francisco river, transforming the region into one more Brazilian California, with several irrigation projects in production, deployment or study. With public investment, occurred recovery and speculation of land on the banks of the Velho Chico, especially the regions of the Middle and Lower-middle São Francisco, where they are located, respectively, irrigation projects of Baixio de Irecê and Salitre, considered two transpositions Bahia according to the volumes of water required for the implementation of these projects. The creation of these irrigation schemes led to the dispossession and the desterreamento of hundreds of peasant families, who throughout history have experienced different deterritorializing processes according to the state actions...